2017
DOI: 10.1155/2017/6509493
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Paediatric Motor Neuron Disorders: Beyond Spinal Muscular Atrophy

Abstract: Paediatric motor neuron diseases encompass a group of neurodegenerative diseases characterised by the onset of muscle weakness and atrophy before the age of 18 years, attributable to motor neuron loss across various neuronal networks in the brain and spinal cord. While the genetic underpinnings are diverse, advances in next generation sequencing have transformed diagnostic paradigms. This has reinforced the clinical phenotyping and molecular genetic expertise required to navigate the complexities of such diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 153 publications
0
16
0
2
Order By: Relevance
“…Studies have shown that mutations in dynein-dynactin complex lead to axonal Charcot-Marie-Tooth type 2 (CMT2) and lower motor neuron disease [61]. Additionally, dysregulation of this complex may be fundamental to spinal and bulbar muscular atrophy (Kennedy disease) [61]. Dynactin mutations have led to a decrease in the dynein complex activity in the motor neurons of ALS patients as well [61].…”
Section: Role In Amyloid Diseasesmentioning
confidence: 99%
“…Studies have shown that mutations in dynein-dynactin complex lead to axonal Charcot-Marie-Tooth type 2 (CMT2) and lower motor neuron disease [61]. Additionally, dysregulation of this complex may be fundamental to spinal and bulbar muscular atrophy (Kennedy disease) [61]. Dynactin mutations have led to a decrease in the dynein complex activity in the motor neurons of ALS patients as well [61].…”
Section: Role In Amyloid Diseasesmentioning
confidence: 99%
“…Infantile hereditary lower motor neuron diseases (LMND) harbor a large group of disorders characterized by muscular weakness and atrophy due to lower motor neuron degeneration (Teoh et al, ). The implementation of high‐throughput sequencing into clinical practice has unveiled a number of clinical conditions designated as infantile LMND, or non‐5q spinal muscular atrophy (non‐5q‐SMA) resembling spinal muscular atrophy (SMA) but without deletions or point mutations in SMN1 (Peeters, Chamova, & Jordanova, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous work, 48.4% of the individuals failed to show a deletion/mutation in SMN1 in the routine SMN1 deletion/point mutation analysis of 3,465 suspected SMA individuals (Karakaya et al, ). These non‐5q‐SMA phenotypes may also exhibit additional neurologic and multisystemic features (Teoh et al, ). In particular, cerebellar and brainstem involvement in individuals with non‐5q‐SMA was described extensively and defined as a distinct syndrome, pontocerebellar hypoplasia (PCH1A‐D) due to mutations in VRK1 (Renbaum et al, ), EXOSC3 (Wan et al, ), EXOSC8 (Boczonadi et al, ) and SLC25A46 (Wan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Os sintomas podem ter início precocemente, ainda no período pré-natal, quando se observa diminuição dos movimentos fetais, ao nascimento ou nos primeiros seis meses de vida, evoluindo com paralisia muscular progressiva e simétrica, sendo esta mais proximal do que distal 8,9 . O controle da coluna cervical é comprometido de tal forma que os pacientes têm dificuldade em sustentar a cabeça e não conseguem sentar sem auxílio 3,9 .…”
unclassified
“…A tosse e o choro são fracos e, antes de completarem 1 ano de idade, estas crianças perdem a capacidade de deglutir e de se alimentar, desenvolvendo quadro de desnutrição. Todavia, o que as leva à mortalidade em tenra idade são as complicações respiratórias consequentes da disfunção bulbar 8 . Apesar das afecções motoras, a sensibilidade é preservada, assim como o controle ocular e a visão, o que permite que os movimentos dos olhos sejam usados para interação e comunicação…”
unclassified